IMPLEMENTATION OF CUSTOMER RELATIONSHIP MANAGEMENT (CRM) ON PATIENT LOYALTY MEDIATED BY CUSTOMER BONDING AT PUSKESMAS JELBUK JEMBER - Anggraeni, Reni Septa; Haris Hermawan; Mohammad Thamrin (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: The community members who use healthcare services at the puskesmas are expected to show commitment to the services provided by the puskesmas. This commitment is one form of patient loyalty. Patient loyalty is crucial because the puskesmas is a primary healthcare facility responsible for providing basic services to both patients enrolled in the BPJS Health program and the general public. Novelty research is the development of a research model that uses customer bonding variables as an intervening variable which has not been developed by previous researchers. Method: The study population consisted of BPJS patients who visited Puskesmas Jelbuk during 2024. Sampling was done using the saturated sampling method with 100 respondents. Data analysis techniques using SEM PLS. Results: The results showed: (1) CRM had a positive and significant influence on patient loyalty. (2) Customer bonding had a positive and significant influence on patient loyalty. (6) The indirect effect test showed a positive and significant influence of CRM on patient loyalty through customer bonding.